THE CHARACTER AND MORAL VALUE IN “SPARE PARTS” BY JOSHUA DAVIS - Sufi Arqom; Engliana Engliana (Universitas Indraprasta PGRI, 2019)
Abstract: The purpose of the research is to analyze the character, moral values and the correlation between character and moral values in the movie Spare Parts by Joshua Davis. The methods used in the research are qualitative by using Theory of Creswell and research that aims to describe the character and moral values and psychological approach by using theory of Stelle and Stepshon & Ling, contained in the movie Spare Parts. 1) The data obtained then analyzed and clarified based on the protagonist found in Oscar Vasquez, Dr. Cameron, Gwen Kolinsky and Karen Lowry, antagonist can be found in Hector, secondary character found in Christian Arcega, Luis Aranda, Lorenzo Santillan And Karla, extras character found in Maddy Kolinsky, round character can be found in Pablo Santillan, and flat character can be found in Mrs. Vasquez and moral values divided to honesty, solidarity, altruism, and diligence, 2) The important character is Oscar Vasquez, Dr. Cameron, Gwen Kolinsky and Karen Lowry they are protagonists and involved along the movie, most significant moral values of the movie are honesty and solidarity those have largest amount of percentage and most important moral values are also honesty and solidarity those have big effect toward successful of the story in the movie also in their real life. It is also found that there is the correlation between character and moral values, can unite them to reach their passion and goal to win the robotics competition. Key Words: Character, Moral Value, Correlation Character and Moral Value.